Analisis Pengukuran Daya Saing Destinasi Wisata Berbasis Tourism and Travel Competitiveness Index - Yuviani Kusumawardhani (Akademi Pariwisata Bunda Mulia, 2019)
ABSTRACTPorter's theory of international competitiveness departs from his belief that classical economic theory that explains comparative advantage is inadequate. A country's competitiveness is determined by the ability of industries to innovate and improve their capabilities. Tourism is currently the star for countries to improve their performance. The Travel and Tourism Competitiveness Index can provide support for countries that want to improve their tourism competitiveness. Literature study in a journal entitled